Hypernasality in singing among children with cleft palate: a preliminary study - Peter, Sabrina; Rahman, Zainal Ariff Abdul; Pillai, Stefanie (Elsevier, 2019)
The aim of this study was to document differences in hypernasality during speaking and singing among children with cleft palate and to compare nasality score ratings of trained and untrained listeners. Twenty subjects with cleft palate aged between 7 and 12 years participated in this study. Audio recordings were made of the children reading a passage and singing a common local song, both in the Malay language. The degree of hypernasality was judged through perceptual assessment. Three trained listeners (a speech therapist, a classical singer, and a linguistic expert – all academicians) and two untrained listeners (a cleft volunteer worker and a national high school teacher) assessed the recordings using a visual analogue scale (VAS). Inter-rater and intra-rater reliability for hypernasality in both speaking and singing were verified using the intra-class correlation coefficient (ICC). A significant reduction in hypernasality was observed during singing as compared to speaking, indicating that hypernasality reduces when a child with cleft palate sings. The act of singing significantly reduces hypernasality. The outcome of this study suggests that children with cleft palate would benefit from singing exercises to ultimately reduce hypernasality. However, future research is needed to objectively measure nasality in singing compared to speaking. © 2019 International Association of Oral and Maxillofacial Surgeons